2017
DOI: 10.1097/won.0000000000000374
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive Hyperbaric Oxygen Therapy for Healing of Chronic Diabetic Foot Ulcers

Abstract: Adjunctive HBOT improved wound healing in persons with DFU. Therapy also reduced the risk of amputation of the affected limb. We assert that at least 20 HBOT sessions are required to be effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
100
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(112 citation statements)
references
References 39 publications
3
100
0
6
Order By: Relevance
“…Chen et al . also reported a significantly ( P =0.010) lower amputation rate in participants allocated to HBOT (5%) compared to controls (11%), although it was not possible to replicate their statistical findings. In the other four trials it was reported that the requirement for major amputation was not significantly different between groups .…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Chen et al . also reported a significantly ( P =0.010) lower amputation rate in participants allocated to HBOT (5%) compared to controls (11%), although it was not possible to replicate their statistical findings. In the other four trials it was reported that the requirement for major amputation was not significantly different between groups .…”
Section: Resultsmentioning
confidence: 92%
“…Also one further trial did not clarify whether minor or major amputations were reported . For the purpose of the present meta‐analysis it was assumed the data represented major amputations, although it was not possible to confirm this despite contacting the authors . Finally, the funnel plot for the primary outcome suggested the possibility of publication bias owing to the asymmetrical distribution of data points.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…A limitation of this review is the small size and number of RCTs and nonrandomized studies that were available for inclusion. Unfortunately, most authors did not respond to our request for additional data, which also led to the exclusion of two major RCTs . Nevertheless, this review currently represents the best available evidence for this specific subgroup of patients.…”
Section: Discussionmentioning
confidence: 99%